PEMBUATAN BAHAN AJAR BERBASIS MODUL PADA MATAKULIAH MEDIA PEMBELAJARAN DI JURUSAN TARBIYAH STAIN SULTAN QAIMUDDIN KENDARI - Ambar Sri Lestari (Institut Agama Islam Negeri Kendari, 2014)
Media in teaching and learning is one module in the form of teachingmaterials. Teaching materials are all kinds of materials that are used tohelp teachers / instructors in carrying out teaching and learningactivities in the classroom. Modules can be viewed as a medium or asteaching material, but in this study modules are seen as the mediumused to convey the material teachers. The module is a tool or a learningtool containing materials, methods, limitations, and how to evaluatesystematically designed and appealing to attain competency / subcompetencies expected in accordance with the level of complexity.Keywords: Modules, Subjects, Learning Media